2012
DOI: 10.1002/tox.21785
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to di‐(2‐ethylhexyl)‐phthalate leads to cognitive dysfunction and phospho‐tau level increase in aged rats

Abstract: Di-(2-ethylhexyl)-Phthalate (DEHP) can affect glucose and insulin homeostasis in periphery and lead to insulin resistance, especially exposure of DEHP during critical developmental period. Given the potential relationship between insulin resistance and pathogenesis of Alzheimer's disease (AD) in elderly life, we investigated the relationship between perinatal DEHP exposure and AD pathogenesis. Our results suggested that perinatal exposure to DEHP can affect the expression of insulin and insulin-Akt- GSK-3β sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Fish exposed to diethylhexyl phthalate (DEHP) showed reduced neurotransmitter activity and behavioral changes [ 145 ]. DEHP was shown to significantly inhibit acetylcholinesterase activity and upregulate glial fibrillary acidic protein as well as myelin basic protein in zebrafish embryos [ 146 ]; it also was observed to cause cognitive dysfunction and increased phosphorylation of tau protein in aged rats prenatally exposed to DEHP [ 147 ]. Efforts are ongoing to reduce and replace the use of these chemicals, which also may reduce potential adverse impacts on human health of DEHP acting alone or in synergy with other common industrial compounds such as BPA.…”
Section: Other Industrial and Commercial Pollutantsmentioning
confidence: 99%
“…Fish exposed to diethylhexyl phthalate (DEHP) showed reduced neurotransmitter activity and behavioral changes [ 145 ]. DEHP was shown to significantly inhibit acetylcholinesterase activity and upregulate glial fibrillary acidic protein as well as myelin basic protein in zebrafish embryos [ 146 ]; it also was observed to cause cognitive dysfunction and increased phosphorylation of tau protein in aged rats prenatally exposed to DEHP [ 147 ]. Efforts are ongoing to reduce and replace the use of these chemicals, which also may reduce potential adverse impacts on human health of DEHP acting alone or in synergy with other common industrial compounds such as BPA.…”
Section: Other Industrial and Commercial Pollutantsmentioning
confidence: 99%
“…In an animal study involving a rat model, phthalate exposure was shown to impair cognitive function and increase the level of phspho-Tau, a precursor of AD development, in exposed rat offspring [129]. Currently no definitive epidemiological studies have been conducted with phthalates and neurodegenerative diseases.…”
Section: Epidemiologic and Experimental Evidence Of Brain Health Dmentioning
confidence: 99%
“…Therefore, perinatal BPA exposure might be a risk factor for the long-term neurodegenerative changes in offspring male mice [206]. Phthalates have been demonstrated to induce nuclear transcription factors that are activators of telomerase reverse transcriptase (TERT), which has a role in tumor promotion [207], increase levels of phospho-tau, a precursor to AD [129], and affects dendritic spine density [120]. Recent reviews have also indicated disruption of thyroid homeostasis, disruption of calcium signaling, peroxisome proliferator-activate receptors (PPAR) activation, and adverse lipid metabolism as other potential mechanism [208].…”
Section: Mechanisms Of Actions Of Estrogenic Endocrine Disruptors mentioning
confidence: 99%
“…However, direct evidence supporting a causal role is scarce and even conflicting. For example, some studies showed that perinatal or adult exposure to phthalates lead to elevated blood glucose, reduced serum insulin, impaired glucose tolerance and insulin secretion in rodents [ 11 - 14 ] while others found the opposite results [ 15 ] or no effect at all [ 16 ]. Moreover, because the animals used in the studies did not develop type 2 diabetes, a causal link to the disease is still hypothetical.…”
Section: Introductionmentioning
confidence: 99%